INTEGRASI ‘GLOBAL CITIZENSHIP EDUCATION’ DALAM PEMBELAJARAN KERAGAMAN DI SMK BUKIT ASAM TANJUNG ENIM - Indarti, Sri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The challenges of life in the twentieth century became the concern of UNESCO to provide the world's students to be able to face all the problems and the ability to deal with local and global issues. Global Citizenship Education (GCE) teaches understanding of tolerance, skills and value for learners to work together to solve local, regional, national and global problems. GCE focuses on understanding and solving problems related to social issues, politics, economics, human rights, gender equality, terrorism, poverty, natural resource management. GCE offers learning that fosters awareness of engagement in solving local life issues to bring about global change through participatory strategies and methods. Implementation of holistic and integrative learning that prioritizes critical thinking, dialogue and action in the activities and everyday life of learners. Learning activities outside the classroom is one alternative that can be applied to achieve the goals of CGE. Cognitive, social-emotional and behavioral development are the three major dimensions of GCE. GCE at SMK Bukit Asam is integrated in all subjects, intra and extra curricular activities and concrete actions by collaborating and networking local, regional, national and global. Becoming an active member of ASPnet becomes a medium to be active in applying GCE.  Key words: Global Citizenship Education, UNESCO, Holistic, ASPnet, SMK Bukit Asam